Evaluation of efficacy and safety of Lacticaseibacillus rhamnosus LRa05 in the eradication of Helicobacter pylori: a randomized, double-blind, placebo-controlled trial - Niu, Yue; Li, Jing; Qian, Hongwei; Liang, Chunli; Shi, Xinyi; Bu, Shurui (Frontiers in Immunology, 2024)
Aim: This study aims to evaluate the efficacy of Lacticaseibacillus rhamnosus LRa05 supplementation in enhancing Helicobacter pylori (H. pylori) eradication rate and alleviating the gastrointestinal side effects associated with bismuth quadruple therapy.Methods: H. pylori-positive patients were randomized to receive levofloxacin-based bismuth quadruple therapy combined either probiotic LRa05 or a placebo for two weeks, followed by LRa05 (1 × 10 10 CFU) or maltodextrin for the next two weeks. H. pylori infection was detected by 13 C breath test pre-and post-treatment. Blood and stool samples were collected at week 0 and week 4 for routine and biochemical analysis, and serum inflammatory markers. Gastrointestinal symptoms were evaluated using the gastrointestinal symptom rating scale (GSRS). Intestinal microbiota was analyzed using 16S rRNA sequencing. The research was listed under the Chinese Clinical Trial Registry (ChiCTR2300072220), and written informed consent was obtained from all participants.Results: The LRa05 group exhibited a trend toward higher H. pylori eradication rates (86.11%) compared to the placebo group (82.86%), though the difference was not statistically significant. Significant reductions in neutrophil count, alanine aminotransferase, aspartate aminotransferase, pepsinogen I, interleukin-6 (IL-6), tumor necrosis factor α (TNF-α) (p < 0.05) suggest that LRa05 supplementation may mitigate inflammation, enhance liver function, and potential aid in early cancer prevention. GSRS symptom scores showed that LRa05 alleviated abdominal pain, acid reflux, bloating, and diarrhea, enhancing patient compliance. Furthermore, 16S rRNA sequencing showed that LRa05 countered the antibiotic-induced disruption of gut microbiota diversity, primarily by increasing beneficial bacteria.Although LRa05 did not significantly improve the success rate of H. pylori eradication therapy, it has the potential to improve liver function and reduced levels of inflammatory markers such as IL-6 and TNF-α in the body, regulating the inflammatory response. In addition, it played a positive role in alleviating the adverse symptoms and gut microbiota disturbances caused by eradication therapy, providing a possible way to improve the overall health of patients and demonstrating promising clinical potential.